Religiosity and Nationalism of Gen Z Muslims: Aspirations and Challenges for Indonesia’s Future - Suprapto, Suprapto; Huda, Miftahul; Millenio, Gifford Adji Akbar (Ulumuna, 2025)
The correlation between religiosity and nationalism has been a paramount issue, particularly in Muslim-majority countries such as Indonesia. Maintaining the spirits of Islam and Indonesia is an arduous effort for young people. This article is based on research into the perceptions and practices of Gen Z Muslims in two prominent tourist islands, Bali and Lombok. The study employed a mixed-method approach, collecting data through questionnaires, in-depth interviews, and focus group discussions with young Muslim activists. The study demonstrates the high level of religiosity and nationalism among young Muslims and a positive correlation between these two values. Religiosity and nationalism support and reinforce each other. Gen Z's vision of Indonesia's future also shows synergistic ideas of religiosity and nationalism. Therefore, excessive apprehension about a clash between religiosity and nationalism is futile. However, continuous efforts to maintain a balanced spirit of religiosity and nationalism are imperative to prevent extreme religious nationalism, which hampers the development of democracy.